CHASING TRENDS, SPENDING FAST: THE ROLE OF HEDONIC LIFESTYLE AND FOMO IN IMPULSIVE BUYING AMONG GEN Z - Suarmaja, Ida Bagus Koman; Kusuma, Gede Wira (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study explores the relationship between FOMO, hedonic lifestyle, and impulsive buying behavior among Generation Z. It investigates how social media exposure and digital consumer trends shape purchasing habits. The primary research question in this study is to what extent do FOMO and hedonic lifestyle influence impulsive buying among Generation Z? Despite previous studies on impulsive buying, research linking hedonic lifestyle and FOMO specifically within Generation Z remains scarce. This study fills the gap by providing empirical evidence on their interrelated effects. A quantitative method is employed using survey-based questionnaires distributed to a purposive sample of Generation Z consumers. Data is analyzed through multiple regression models to determine the significance of FOMO and hedonic lifestyle in predicting impulsive buying behavior. The results indicate that both FOMO and hedonic lifestyle significantly impact impulsive buying behavior. Individuals experiencing high FOMO are more likely to make unplanned purchases due to social influences, while those with a hedonic lifestyle tend to prioritize immediate gratification in their consumption habits. This study concludes that FOMO and hedonic lifestyle have a strong influence on impulsive buying tendencies in Generation Z. The findings contribute to understanding consumer behavior in digital environments and offer insights for marketers in designing strategies tailored to this demographic.